SYSTEM-STRUCTURAL ANALYSIS AS A TOOL FOR IMPROVING THE EFFICIENCY OF PRIVATIZATION OF THE UKRAINIAN BANKING SECTOR - Бебко, Світлана Вікторівна; Шіковець, Катерина Олексіївна; Харлім, Валерій Михайлович (Journal of Strategic Economic Research, 2024)
The article highlights the specifics and key elements of system-structural analysis as a tool for improving the efficiency of privatization of the banking sector of Ukraine. The main types of structures and stages of system-structural analysis based on the principles of the systemic approach are stated. The system-structural analysis of the banking sector of Ukraine is carried out. The banking system of Ukraine is considered, taking into account the preparation for the privatization of banks with a controlling stake in state ownership during the military invasion, as a set of interconnected elements that interact with each other in order to achieve certain goals, its mission and role are indicated. The dynamics of changes in the number of banks from 2017–2024, the banking classification adopted in Ukraine and the structure of the banking system of Ukraine in 2024 are determined. At the stage of grouping the elements into substructures, the status of the systemic importance of banks and their profitability are analyzed. In establishing various links and relationships between the elements, substructures and the whole, Ukrgasbank and Sense Bank are considered as elements of the whole. It has been determined that Ukrgasbank and Sense Bank are two systemic state-owned banks that have; 4% and 6% of net assets, respectively; a wide network of branches; 2.894 million and 1.548 million depositors; 3.44 and 3.43 overall rating; 12th and 13th place among all Ukrainian banks; 3.4 and 3.2 depositors' loyalty; 6th and 9th place in the ranking of retail deposits; sufficient regulatory capital; real estate and liquid property. Thus, it has been established that Ukrgasbank and Sense Bank are state-owned banks that have: a developed customer base, a banking business that works and generates profit, real estate, and a well-known brand in the Ukrainian market, which is why they are attractive assets even in wartime.